2021
DOI: 10.1093/cid/ciab229
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Coronavirus Disease 2019 (COVID-19) Vaccine on Asymptomatic Infection Among Patients Undergoing Preprocedural COVID-19 Molecular Screening

Abstract: Background Several vaccines are now clinically available under emergency use authorization in the United States and have demonstrated efficacy against symptomatic COVID-19. The impact of vaccines on asymptomatic SARS-CoV-2 infection is largely unknown. Methods We conducted a retrospective cohort study of consecutive, asymptomatic adult patients (n = 39,156) within a large United States healthcare system who underwent 48,333 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
131
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(142 citation statements)
references
References 10 publications
9
131
0
2
Order By: Relevance
“…This also makes it difficult to compare estimates coming from different areas. A recent retrospective cohort study by Tande et al [29] has established a vaccine effectiveness of 80% (95% CI: 56-91%) against asymptomatic SARS-CoV-2 infection after two doses of the mRNA vaccines. An observational study from Israel [20] reported a higher estimate: in the period of ≥7 days after the second dose of BNT162b2 the vaccine effectiveness in the elderly was 88.5% (95% CI: 86.4-90.3%).…”
Section: Discussionmentioning
confidence: 99%
“…This also makes it difficult to compare estimates coming from different areas. A recent retrospective cohort study by Tande et al [29] has established a vaccine effectiveness of 80% (95% CI: 56-91%) against asymptomatic SARS-CoV-2 infection after two doses of the mRNA vaccines. An observational study from Israel [20] reported a higher estimate: in the period of ≥7 days after the second dose of BNT162b2 the vaccine effectiveness in the elderly was 88.5% (95% CI: 86.4-90.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, the decrease in the number of people with severe COVID-19 infection, mediated by vaccination, will also decrease the duration time of transmission and contagiousness, indirectly reducing also the contagion between men. In addition, evidence shows also a reduction in the number of asymptomatic cases in vaccinated individuals (Tande et al 2021). Moreover, new variants of SARS-CoV-2 have recently been identified in the United Kingdom and South Africa (Conti et al 2021;Giovanetti et al 2021).…”
Section: Vaccines Mrna Against Covid-19mentioning
confidence: 99%
“…With over one million refugees on its territory, Lebanon also hosts the highest per capita number of refugees worldwide [3], a population highly vulnerable to large SARS-CoV-2 outbreaks [4]. At this stage, mass vaccination with the recently available and highly efficacious COVID-19 vaccines [5][6][7][8][9] brings hope to control infection spread and mitigate its profound impact, especially with the emerging 'real-world' evidence of their high effectiveness in reducing both symptomatic and asymptomatic disease [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%